One-Dimensional Large-Strain Nonlinear Consolidation of Overconsolidated Clays with a Threshold Hydraulic Gradient - Chuanxun Li; Jinyang Xiao; Yang Yang; Wenbing Wu (Advances in Civil Engineering)
The existence of the threshold hydraulic gradient in clays under a low hydraulic gradient has been recognized by many studies. Meanwhile, most nature clays to some extent exist in an overconsolidated state more or less. However, the consolidation theory of overconsolidated clays with the threshold hydraulic gradient has been rarely reported in the literature. In this paper, a one-dimensional large-strain consolidation model of overconsolidated clays with consideration of the threshold hydraulic gradient is developed, and the finite differential method is adopted to obtain solutions for this model. The influence of the threshold hydraulic gradient and the preconsolidation pressure of overconsolidated clay on consolidation behavior is investigated. The consolidation rate under large-strain supposition is faster than that under small-strain supposition, and the difference in the consolidation rate between different geometric suppositions increases with an increase in the threshold hydraulic gradient and a decrease in the preconsolidation pressure. If Darcy’s law is valid, the final settlement of overconsolidated clays under large-strain supposition is the same as that under small-strain supposition. For the existence of the threshold hydraulic gradient, the final settlement of the clay layer with large-strain supposition is greater than that with small-strain supposition.